1996
DOI: 10.1136/jnnp.61.2.200
|View full text |Cite
|
Sign up to set email alerts
|

A special form of cerebral lacunae: expanding lacunae.

Abstract: The case of a 42 year old man with headache, blurred vision, and diplopia allowed the description of a particular form of cerebral lacunae-that is, expanding lacunae. Brain MRI showed hydrocephalus and multiple lesions in the thalamomesencephalic region. The radiological features of these lesions were similar to the histological brain coronal section of a case reported in 1983 in which expanding lacunae were related to a dilatation of the perivascular spaces and a focal segmental necrotising angiitis. The rol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
43
1
1

Year Published

1999
1999
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 9 publications
0
43
1
1
Order By: Relevance
“…Although MR imaging is suitable to differentiate the three fundamental types of brain lacunae, [5,8,11] a differential diagnosis that includes other intracranial cystic lesions in the same location, in particular those due to parasites (echinococcosis, cryptooccocosis, and cysticercosis), has to be considered. [10] Cryptococcus neoformans has a predilection for the brain perivascular spaces, [2,22] but cryptococcosis usually occurs against the background of acquired immunodeficiency syndrome and is associated with CSF abnormalities and extensive changes and contrast enhancement of adjacent brain parenchyma on imaging studies, which were absent in our patients. Lack of calcification and contrast enhancement is also unusual for cysticercosis, which has a predilection for the ventricular or subarachnoid spaces.…”
Section: Discussionmentioning
confidence: 55%
See 3 more Smart Citations
“…Although MR imaging is suitable to differentiate the three fundamental types of brain lacunae, [5,8,11] a differential diagnosis that includes other intracranial cystic lesions in the same location, in particular those due to parasites (echinococcosis, cryptooccocosis, and cysticercosis), has to be considered. [10] Cryptococcus neoformans has a predilection for the brain perivascular spaces, [2,22] but cryptococcosis usually occurs against the background of acquired immunodeficiency syndrome and is associated with CSF abnormalities and extensive changes and contrast enhancement of adjacent brain parenchyma on imaging studies, which were absent in our patients. Lack of calcification and contrast enhancement is also unusual for cysticercosis, which has a predilection for the ventricular or subarachnoid spaces.…”
Section: Discussionmentioning
confidence: 55%
“…As well, no clinical correlate was found by Ogawa, et al, [17] in two cases of dilated perivascular spaces demonstrated by MR imaging in cerebral hemispheric white matter, although the results of a biopsy sample confirmed one of these cases. Also, in a 42-year-old man described by Homeyer, et al, [10] in whom a diagnosis of expanding lacunae based on MR imaging and negative laboratory examinations for parasites had been made, the expanding lacunae had a mesencephalothalamic distribution, causing stenosis of the aqueduct and triventricle hydrocephalus. The clinical features in that case included headache, blurred vision, diplopia, paresthesias to the upper limbs, skew deviation, and Parinaud's syndrome.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Fibrosis and obstruction were thought to be the cause of dilatation of perivascular spaces in basal ganglia, based on light microscopy, scanning and transmission electron microscopy and direct visualization of etched paraffin blocks of post mortem specimens of brain by Pollock et al 3 . The other proposed mechanisms include disturbance of the drainage of interstitial fluid due to abnormal cerebrospinal fluid (CSF) circulation 8 , repeated mechanical trauma from CSF pulsations 12 , spiral elongation of ectatic penetrating blood vessels 13 , increased fluid exudation consequent to abnormal vascular permeability 14 and an ex vacuo effect secondary to ischemic perivascular tissue injury 15 . Although usually asymptomatic, giant perivascular spaces may be associated with non-specific symptoms.…”
Section: Discussionmentioning
confidence: 99%